Life cycle energy-economy-environmental evaluation of coal-based CLC power plant vs. IGCC, USC and oxy-combustion power plants with/without CO2 capture. Issue 5 (October 2021) - Zhao, Ying-jie; Duan, Yuan-yuan; Liu, Qian; Cui, Yang; Mohamed, Usama; Zhang, Yu-ke; Ren, Zhi-li; Shao, Yi-feng; Yi, Qun; Shi, Li-juan; Nimmo, William
Abstract: Coal-based chemical looping combustion (CLC) power plant presents itself as a promising technology due to its low energy penalty which is associated with its inherent CO2 capture process. However, most evaluations and comparisons (energy efficiency, economic, and environmental aspects) of the CLC power plant generally were focused on the power plant operation stage. Life cycle assessment (LCA) method with a "cradle to gate" model involving power plant construction, operation, and decommissioning stage, of coal-based power plants was established. Following that the resource consumption, energy consumption, environmental impact potential, and economic performance in the life cycle, were comprehensively compared between the coal-based CLC power plant and other plants such as IGCC, USC and oxy-combustion power plants with and without (w/o) CO2 capture, to find out the potential and deficiency of the coal-based CLC power plant in a life cycle perspective. Results showed that energy resource consumption accounts for the largest proportion of the total resource consumption (81.88–91.89%) in six coal-fired power plants. Among the environmental impact potentials, smoke and dust potential (SAP) has the highest value while eutrophication potential (EP) resulted in the lowest in six coal-based power plants. CLC presented resource depletion indicator, energy payback ratio and the total life cycle costs, at 4.79 × 10 −6 kWh/person/day, 3.22, and 0.138 /kWh, respectively. These power plants were ranked from highest to lowest according to their sustainability as the following USC, CLC, IGCC, oxy-CCS, USC-CCS, and IGCC-CCS. However, CLC presents the best sustainability in all coal-based power plants with CO2 capture. The CLC power plant will be one of the most attractive options for carbon reduction in coal-based power systems, as the development of CLC technology further improves energy efficiency and economic performance. The results further demonstrated that the coal-based CLC power plant can solve the issues involving CO2 emission reduction and energy utilization in coal to power generation process from lifecycle viewpoint. Graphical Abstract: ga1 Highlights: Life cycle energy-economic-environmental evaluation of CLC/USC/IGCC/oxy-combustion plants w/o CCS. Resource depletion of CLC is 4.79 × 10 −6 kWh/person/day. CLC shows net energy efficiency & energy payback ratio at 34.8 and 3.22 respectively. CLC presents life cycle costs at 0.138 /kWh. CLC presents the best sustainability in all coal-based power plants with CO2 capture.